Forearm muscle oxygenation during sustained isometric contractions in rock climbers - Jan Kodejška; Michail L. Michailov; Jiří Baláš (Karolinum Press, 2016)
Background. Bouldering and lead climbing are divergent disciplines of the sport of rock climbing. Bouldering moves are short and powerful, whilst sport climbing is longer and require a greater degree of endurance. Aim. The aim of this study was to compare forearm muscle oxygenation during sustained isometric contraction between lead climbers (LC) and boulderers (BO). Methods. Eight BO and twelve LC completed maximal finger flexor strength test and sustained contractions to exhaustion at 60% of maximum voluntary contraction (MVC). Differences between BO and LC in maximal strength, time to exhaustion, force time integral (FTI), and tissue oxygenation (SmO2) were assessed by t-test for independent samples. Results. LC showed significantly lower level of average tissue oxygenation (BO 38.9% SmO2, s = 7.4; LC 28.7% SmO2, s = 7.1) and maximal tissue deoxygenation (BO 25.6% SmO2, s = 8.2; LC 13.5% SmO2, s = 8.5). LC demonstrated significantly lower finger flexor strength (519 N, s = 72) than BO (621 N, s = 142). LC sustained a longer time of contraction (not significantly) (BO 52.2 s, s = 11.5; LC 60.6 s, s = 13) and achieved a similar value of FTI (BO 17421 Ns, s = 4291; LO 17476 Ns, s = 5036) in the endurance test. Conclusions. The results showed lower deoxygenation during sustained contraction in BO than LC despite similar FTI, indicating different local metabolic pathways in both groups.